An Innovative Approach Continual Improvement of CO-PO Attainments - Rajendra Prasad, M.; Anuradha, M. N. L.; Govardhan Reddy, J. (Journal of Engineering Education Transformations, 2020)
With the growing quantity and quality of information on the internet, the trends in teaching have accelerated rapidly in recent years. The teacher's role has changed from that of knowledge-transmitter to consultant, guide, coach, and facilitator. The Outcome Based Education (OBE) Curriculum outlines specific measurable outcomes for each Course. The entire Curriculum focuses on what students can actually do after they complete the Course. In this Curriculum the teacher should focus on helping the students in providing & developing the knowledge and skills that enable them to achieve the clearly defined outcomes. After the completion of the course, attainment of that particular Course is evaluated. In this paper we talk about an innovative methodology for continuous improvement (IMCI) which is implemented at Vidya Jyothi Institute of Technology, Hyderabad that comprises of some activities which benefit the students to improve their academic performance there by increasing the attainment of that particular course. This increases the CO-PO Attainment values.